Spectroscopic signatures of states in the continuum characterized by a joint experimental and theoretical study of pyrrole - Mukherjee, Madhubani; Ragesh Kumar, T P; Ranković, Miloš; Nag, Pamir; Fedor, Juraj; Krylov, Anna I (The Journal of chemical physics, 2022)
We report a combined experimental and theoretical investigation of electron-molecule interactions using pyrrole as a model system. Experimental two-dimensional electron energy loss spectra (EELS) encode information about the vibrational states of the molecule as well as the position and structure of electronic resonances. The calculations using complex-valued extensions of equation-of-motion coupled-cluster theory (based on non-Hermitian quantum mechanics) facilitate the assignment of all major EELS features. We confirm the two previously described π resonances at about 2.5 and 3.5 eV (the calculations place these two states at 2.92 and 3.53 eV vertically and 2.63 and 3.27 eV adiabatically). The calculations also predict a low-lying resonance at 0.46 eV, which has a mixed character-of a dipole-bound state and σ* type. This resonance becomes stabilized at one quanta of the NH excitation, giving rise to the sharp feature at 0.9 eV in the corresponding EELS. Calculations of Franck-Condon factors explain the observed variations in the vibrational excitation patterns. The ability of theory to describe EELS provides a concrete illustration of the utility of non-Hermitian quantum chemistry, which extends such important concepts as potential energy surfaces and molecular orbitals to states embedded in the continuum.